Quantitative XRD characterisation and gas-phase photocatalytic activity testing for visible-light (indoor applications) of KRONOClean 7000®. Issue 124 (1st December 2015) - Tobaldi, D. M.; Seabra, M. P.; Otero-Irurueta, G.; de Miguel, Y. R.; Ball, R. J.; Singh, M. K.; Pullar, R. C.; Labrincha, J. A.
Abstract : Carbon-modified commercial anatase (KRONOClean 7000®) was quantitatively characterised with XRD for the first time – full phase composition (both crystalline and amorphous content) and microstructure. Abstract : Carbon-modified commercial anatase (KRONOClean 7000®) was quantitatively characterised with XRD for the first time – full phase composition (both crystalline and amorphous content) and microstructure. The material was found to be bimodal anatase, mostly ∼4 nm diameter, but with a small amount of a larger fraction between ∼12 and 15 nm. Absorption in the visible range was confirmed by UV-Vis analysis, whilst XPS showed that an aromatic carbon compound is at the origin of that absorption. Also, the photocatalytic activity of this commercial nano-TiO2 was assessed, monitoring the abatement of NO x using a white LED lamp, irradiating exclusively in the visible region. Experiments simulated an indoor environment, highlighting the potential of this nano-TiO2 for adoption as a standard for visible-light photocatalytic activity, i.e. applications for innovative interior eco-building materials.